Peran Teknik Informatika Dalam Work From Home (WFH) yang Produktif - Fatimah, Dini Destiani Siti; Pauzi, Hilmi; Gotawa, Ikhsanudin; Apriani, Aulia; Bahari, Albie Firgi; Qorni, Mochamad Rinaldi; Gunawan, Nanda; Kesuma, Muhamad Yoga; Herdiana, Wandi; Sukmawan, Tegar (Institut Teknologi Garut, 2022)
The Coronavirus Disease 19 pandemic caused by the SARS COV 2 Virus in 2021 has not yet been completed, the emergence of a new Delta variant whose spread has accelerated has prompted the government to impose restrictions on emergency community activities in the Java and Bali regions. Making many people have to lose their jobs again for some time, including Hegarmanah Village, Bungbulang District, which also felt the impact of the implementation of the imposition of restrictions on emergency community activities. Previously, the village had carried out the Village Internet program, for each RW it had been facilitated with the internet, it was hoped that this would keep the community productive in completing work with Work From Home. The Work From Home method in Hegarmanah Village is still not well understood by the village community so that the community still has difficulty implementing this method. The Real Work Lecture Group from the Garut High School of Technology took the opportunity to increase the ability of the community to apply the Work From Home method and at the same time increase the ability of the community to prevent coronavirus disease 19. Activities are carried out every week for a total of 4 weeks. Activities carried out with the stages of preparation, implementation, and results. The results obtained from this real work lecture activity are that the community understands more about the Work From Home method as an alternative to working during a pandemic and the community is also more aware of the spread of the corona virus.